Swesaurus – ett svenskt ordnät med fria tyglar - Borin, Lars; Forsberg, Markus (LexicoNordica, 2011)
Swesaurus is a free Swedish wordnet currently under construction in Språkbanken, University of Gothenburg. Swesaurus is constructed by reusing information about lexical-semantic relations in a number of pre-existing freely available lexical resources: SALDO, SDB, Synlex and Swedish Wiktionary. In this article we describe how this existing lexical-semantic information is reused and enriched by utilizing the connections among the lexical resources. We focus in particular on our experiments with turning the graded synonymy relations of Synlex into fuzzy synsets in Swesaurus. The introduction of fuzziness into a wordnet raises many intricate methodological and theoretical questions, which are discussed and illustrated in the article.